Attenuation coefficients for fibrous self-compacting concrete in the energy range of 50-3000keV - Claudio Carvalho Conti; Willy Bento; Luzianete Amaral Magalhães (Brazilian Journal of Radiation Sciences, 2017)
The fibrous self-compacting concrete is a high performance concrete with uniformly distributed iron fibers, developed and characterized by Maragon (2006 and 2009). Transmission measurements, with 137Cs and 60Co sources were performed for the attenuation coefficients determination for both ordinary and fibrous self-compacting concretes. The results were compared to each other and to the values found in the literature for ordinary concrete. The mass attenuation coefficient for the fibrous self-compacting concrete showed to be higher than those for ordinary concrete of about 5%, depending on the gamma energy. However, it should be noted that the density of fibrous self-compacting concrete is higher than ordinary concrete, 2.4 g/cm3 and 1.9 g/cm3 respectively, increasing still further the difference in mass attenuation coefficient. In addition to that, by using Monte Carlo simulations, with MCNP5 Monte Carlo computer code, the data was extended to the 50-3000 keV gamma energy range.